Strategy-as-practice and micro-foundations - Regnér, Patrick (Henry Stewart Talks, 2014)
Micro-foundations and strategy-as-practice, Strategy content, Strategy process, Micro-foundations research in strategy-as-practice, Capabilities, Operational capabilities, Dynamic capabilities, Micro-foundations, Organizational and managerial processes, Apple/iPhone example, Research opportunities, References